ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU PADA BADAN USAHA MILIK DESA (BUMDES) PELITA HIDUP COKLAT KOBAR DESA KOTOWUJI BARAT KABUPATEN NAGEKEO - Bude, Agustina; Soleiman, Iriany Dewi; Sayang, Sabulon (Jurnal Riset Ilmu Akuntansi, 2024)
The purpose of this study was to determine the control of raw material supplies for the smooth production process at Pelita Hidup Kobar Village Owned Enterprises (BUMDES). The method used in this research is descriptive quantitative. Data collection techniques used in this research are through observation, interviews, documentation and literature study. Data analysis techniques in this study for raw material inventory control use the Economic Order Quantity (EOQ), Safety Stock (SS) and Reorder Point (ROP) methods. The results of the study showing that, controlling the supply of raw materials at Pelita Hidup Kobar Village Owned Enterprises (BUMDES) is not optimal. Where, inventory calculations with the BUMDES Pelita Hidup policy show that orders are made 24 times in one year with an average number of purchases of 74 kg of cocoa by issuing an inventory cost of IDR 641,921. Meanwhile, using the Economic Order Quantity (EOQ) method shows that the most economical number of orders for cocoa raw materials is 279 kg of cocoa with 6 orders in one year and only spends an inventory cost of Rp. 308,620. This means that the inventory costs incurred by BUMDES Pelita Hidup are greater than the inventory costs using the EOQ method. BUMDES Pelita Hidup Coklat Kobar has not implemented Safety Stock or safety stock and Reorder Point in its policies, resulting in a shortage of cocoa raw material supplies which resulted in the production process not running smoothly. According to the EOQ method, a safety stock of 322 kg of cocoa raw material must remain at BUMDES Pelita Hidup and must place an order again (ROP) for cocoa raw material when the raw material is at the point of 35 kg of cocoa. Orders must be made before the supply of cocoa raw materials in the warehouse runs out.